HISTORY, EDUCATION, MAPS, STATISTICS, PROPAGANDA - GREECE AND OTTOMAN MACEDONIA IN 19th CENTURY (Annual of the Faculty of Philosophy in Skopje, 2016)
After the well-known speech of Ioannis Kolettis in Greek Parliament in January 1844, Macedonia became one of the regions of Ottoman Empire toward which Greece directed its territorial ambitions. Thus, Macedonia became a significant place of the interest for Greek historians and other intellectuals. During the second half of 19th century substantial changes took place in the Greek historiography. During the first two decades of Greek independent state, Ancient Macedonia and Byzantium were not considered as a part of the Greek past. However, after 1844, Ancient Macedonia and Byzantium became an important part of Greek heritage. The reason was very simple. Both of them were used for proving that Macedonia was a historical Greek land. So, this Ottoman region should become a part of the future expanded Greek state. On the other hand, the territory of the ancient Macedonian kingdom was used by the Greek intellectuals, in cartography, to prove that the northern part of Modern Macedonian region was not a historical Macedonia. However, ethnic composition of Macedonian population did not fit Greek interest. The Greek population in Ottoman Macedonia was a minor in comparison with the others. That was the main reason for creation of Athens society for the expansion of Greek education.
Keywords: MACEDONIA; GREECE; MAPS; STATISTIC; PROPAGANDA